(untitled) (Italiano LinguaDue, 2016)
La prima edizione del Vocabolario milanese-italiano di Francesco Cherubini (1814) si ispira alle teorie del Cesarotti, che considerava i dialetti come importante fonte per l’arricchimento della lingua nazionale. Il saggio mette a confronto i criteri e gli orientamenti lessicografici del Vocabolario di Cherubini con i vocabolari settecenteschi di altre aree dialettali da lui utilizzati e ne evidenzia elementi comuni ed elementi di novità. Cherubini (1814) in the history of the first dialect lexicography The first edition of the Milanese-Italian Dictionary by Francesco Cherubini (1814) was inspired by the theories of Cesarotti, who considered dialects to be an important source for the enrichment of the national language. The essay compares the lexicographical criteria and guidelines of Cherubini’s Dictionary with Dialect Dictionaries from the eighteenth century from other dialect areas that he used, and identifies common and new elements.